Brand Sustainability and Consumer Behaviour in Luxury Fashion: Insights from the Golden Goose Case Study - Ottaviani, Alice (My University, 2025)
In recent years, sustainability has emerged as a strategic measure in addressing various social and environmental challenges associated with the fashion industry. It is expected of brands to demonstrate ethical, environmentally responsible practices and total transparency in their com- munications. Despite the increased efforts of fashion companies to embrace sustainability val- ues, these efforts remain undervalued, particularly in the luxury sector. The present thesis ex- plores the influence of sustainability initiatives on consumer perception and purchase intention. The analysis is grounded in a qualitative approach, with a case study on Golden Goose, an Italian luxury fashion brand recognised and awarded for its craftsmanship and sustainable innovation. It is based on seven semi-structured interviews conducted with a sample of seven Italian con- sumers of the brand. The data were collected via video calls and then analysed using thematic analysis, with the aim of identifying patterns related to brand trust, brand value and purchase intention. Theoretically, the research is grounded on a series of interdependent concepts including corpo- rate sustainability, stakeholder theory, brand trust, perceived value, and greenwashing. Litera- ture emphasizes that sustainability can make a brand image stronger and also promote customer loyalty; however, both benefits happen if actions are well explained and perceived as genuine. Transparency, credibility, and consistency are therefore crucial. The findings of this study agree with these points: although Golden Goose has launched significant sustainability actions—most notably the Yatay Model 1B and the Forward Store—buyer awareness of such activities was gen- erally poor. This gap between the brand's strategic measures and consumer knowledge restricts the potential of such initiatives to induce a good effect on the intention to purchase, underlining the requirement for concentrated and consistent sustainability communication. Three dimensions of trust have been identified. Firstly, the one based on direct experience with the brand, which arises from direct contact with the product/service. Secondly, there is the trust based on the brand's image and reputation, i.e. its positioning and the values associated with it. Finally, there is an evolving trust, characterised by an initial attitude of openness, which then either weakens or strengthens. The study also found that price and aesthetics play a significant role in influencing purchasing decisions, often prevailing over considerations related to sustainability. In conclusion, this thesis demonstrates how sustainability initiatives can positively influence con- sumers' attitudes towards brands and build loyalty, but this is only possible if such strategies are reliable, transparent and emotionally engaging. This study makes a significant contribution to the academic understanding of sustainability, branding and consumer behaviour in the luxury fashion sector.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälisen liiketoiminnan kandidaattiohjelma|en=Bachelor Programme in International Business|